Low Rates of Pointing in 18-Month-Olds at Risk for Autism Spectrum Disorder and Extremely Preterm Infants: A Common Index of Language Delay? - Sansavini, Alessandra; Guarini, Annalisa; Zuccarini, Mariagrazia; Lee, Jessica Zong; Faldella, Giacomo; Iverson, Jana Marie (Frontiers in Psychology, 2019)
Infants with an older sibling with an Autism Spectrum Disorder diagnosis (Sibs ASD) are at high risk for language delay (LD) as well as infants born preterm, especially those with an extremely low gestational age (ELGA, GA ≤28 weeks). Gestures play a crucial role in language development and delays in gesture production may have negative cascading effects on it. The present exploratory study examined gesture production in 18-month-old infants with different underlying risks for LD. Seventy monolingual US infants (41 Sibs ASD with no eventual ASD diagnosis and 29 infants with a typically developing older sibling -Sibs TD) and 40 monolingual Italian infants (20 ELGA without major cerebral damages, congenital malformations or sensory impairments and 20 full-term - FT infants, GA ≥37 weeks) were included. Both groups were followed longitudinally from 18 to 24, 30, and 36 months (corrected for ELGA infants). A 30-minute mother-infant play session with age-appropriate toys was video recorded at 18 months of age. Deictic (requesting, pointing, showing and giving), conventional, and representational gestures spontaneously produced by infants were coded; rate per 10 minutes was calculated. LD was defined as a score ≤10th percentile on the American English or Italian version of the MacArthur-Bates CDI on at least two time points between 18 and 36 months. Fifteen Sibs ASD and 9 ELGA infants were identified as infants with LD. Sibs ASD-LD and Sibs ASD-no LD produced fewer pointing gestures compared to Sibs TD (p = .038; p = .004); ELGA-LD infants produced significantly fewer pointing gestures than ELGA-no LD (p = .024) and FT (p = .006) infants. Low rates of pointing at 18 months are a marker of LD in Sibs ASD and ELGA infants. The potential implications of reduced pointing production and characteristics of different populations at risk for LD should be considered for understanding the emergence of LD.